EFFECT OF CADMIUM TOXICITY ON GENERAL GROWTH PERFORMANCE PARAMETERS IN WISTAR RATS - Navdeep Kour; Shafiqur Rahman; Shagufta Azmi; Kafil Hussain; Pratiksha Raghuwanshi; Sahil Dutta (Indian Journal of Veterinary and Animal Sciences Research, 2024)
The present study was conducted to elucidate the growth performance changes in Wistar rats given cadmium chloride in different doses at various intervals. Wistar rats (n=12/group) were divided into four groups viz, group I (Control) given normal drinking water whereas group II, III and IV rats were given CdCl2 @ 100, 250 and 500 ppm, respectively for 12 weeks. Animals of all the groups were closely observed through out the period of experiment thrice a day for clinical signs. Daily Feed intake (FI), Body Weights (BW), Body Weight Gain (BWG) and Feed Conversion Ratios (FCR) were recorded. Clinical signs observed upto first 5 weeks were less prominent in all the treatment group rats. After 5 weeks PE, rats of all treatment groups showed varying degree of toxic signs, which included inappetence, dullness, weakness, depression, lethargy, reduced feed intake, decrease in body weight, poor fur condition, loss of hair, change in behaviour, disinclination to move, increased thirst and dehydration. In addition, group IV rats also showed nervous disorders from 9th week onwards. The average values of feed consumption, body weight and body weight gain were significantly lower in all treatment group rats as compared to control group rats in dose and duration dependent manner. Moreover, FCR increased significantly in all treatment groups from 4th week PE than control group rats upto the end of trial.